Rendre la parole. Quand les victimes mettent en récit les violences sexuelles dans l’Église catholique - Romaine Girod (Genre, Sexualité et Société)
Based on a corpus of sixteen autobiographies written by victims of sexual violence in the context of the Catholic Church in France, Switzerland and Belgium, this article analyses how sexual violence is put into words. It shows that the autobiographical form produces a space within which authors reappropriate the narration of their experience and position themselves as epistemic subjects – a capacity they have often been denied. The autobiography also opens up a never-ending process of interpretation and reinterpretation of experience, as new hermeneutic resources are acquired which make sexual violence sayable and comprehensible. These texts show the difficulty of naming sexual violence. As individual accounts, they are also collective resources for demanding justice and recognition.